Esthetic root coverage by subepithelial connective tissue graft with management of repeated rupture of palatal arterial bleeding: A rare case report - Archana Agroya; Shilpa Sunil Khanna; Parul Chhabra; Ami Mayurkumar Sheth; Naresh Vattikunta; Navneet Kaur (Wolters Kluwer Medknow Publications, 2021)
Nowadays, patients are much concerned about esthetics of the oro-facial region. Gingival recession is considered as one of the major esthetic problems creating complex situations by compromising oral esthetics. This can be treated successfully by means of several mucogingival surgical procedures which can be used to accomplish satisfactory root coverage without any loss of interdental soft- and hard-tissue height. Grafts are also very useful in such scenarios. Our case reports the connective tissue graft technique used in the treatment of gingival recession. The objective of this case was to evaluate the efficacy of connective tissue graft (CTG) and also to mention the management of complications on the donor site.